The problem of confidence in the Algerian banking sector: 4-24 - داودي , حمزة (Finance and Business Economies Review, 2021)
Confidence is an essential pillar for building relationships and transactions in all fields, especially in the banking sector, because the success of its activities and their development in light of fluctuations and instability requires strong confidence that clients are linked to banks. Confidence with stressful financial conditions may push banks into bankruptcy and plunge the economy into a spiral of problems. Therefore, it is very important to pay attention to the issue of confidence and work to strengthen it. This paper tried to discuss the issue of confidence in the banking sector, its effects and the factors of its construction, then analyze the reality of confidence in the Algerian banking sector, the latter suffering a crisis of confidence that led to its weakness and inability to play its role as an engine of the economy, and one of the most important reasons for undermining the confidence of the sector is the ineffectiveness of regulations and laws Weak financial knowledge and digital confidence for individuals, in addition to poor financial inclusion, information technology and transparency, and the most important measures to restore confidence in the banking sector are the establishment of strict regulations and laws that impose transparency and prudence, as well as building good financial knowledge for individuals, and expanding financial inclusion.